Differences in mandibular disparity between extant and extinct species of metatherian and placental carnivore clades - Echarri, Sebastián (2015)
There are a number of studies relating to skull morphology differences within the carnivoran clades of both placentals and metatherians. It is difficult to compare these studies because of differences in taxonomic sampling, for example some include fossil taxa while others include non-carnivoran placentals. As a consequence, we studied mandible morphology in a broad range of both extant and extinct carnivorous species, including Carnivora, Marsupialia and Sparassodonta to test for differences between these clades. We used geometric morphometrics and two disparity indexes, the variance and Procrustes distances mean. When including fossil species, we found no significant differences for both disparities in some analyses, except after the exclusion of the sabretooth morphotype. This can be explained by the extreme morphology of this morphotype, which increases the variance and reduces the disparity effect of the other species in the analyses. Using Procrustes distances, we found significant differences in disparity distances between Carnivora and Metatheria for most of the analyses. We also found significant differences using the variance index in some analyses. The mandibular disparity in Carnivora is greater than in carnivorous metatherian mammals for most of the cases and this can be related with differences in evolutionary history and constraints of both groups. The pattern found in the mandible is similar to that found in the face of the skull but was not observed in the braincase, due to differences in skull function and mandible function.